Avaliação física, mecânica e microestrutural de beta titanato de alumínio sinterizado por técnica convencional e por two-steps sintering - Domingos, Gustavo Henrique Dos Santos (2020)
Ceramic materials possess several interesting properties that have great applicability in the most various industrial segments. Among them, the refractory sector stands out, which materials with specific properties are widely used. This is the case of Tialite (β-Al2TiO5), whose special characteristics are excellent thermal shock resistance, high melting point, low thermal and electrical conductivity, low coefficient of thermal expansion and low wettability with non-ferrous molten metals. However, there are two problems related to this material during its refrigeration: the eutectoid decomposition in its precursor oxides, Alumina (Al2O3) and Titania (TiO2), after sintering in the temperature range between 750ºC and 1300ºC; and the crack formation in its matrix, occasioning in microstructures with grain size greater than 2 microns, which would cause low mechanical resistance of the material. Therefore, this work proposed to obtain Tialite on a nanometric scale from its precursor oxides from high energy grinding (MAE) for 0, 1, 2, 3 and 4 hours, investigating three different molar proportions - 55:35, 45:45 and 35:55 - ​​Of Alumina and Titania respectively, and a 10% mol of MgO. After obtaining the nanometric scale powders, tablets were formed by uniaxial pressing, with 129,83 , and subjected to conventional sintering at a level of 1550ºC for 2 hours. Then, the same conformation process was applied to another aliquot of the powder, coming from a 2-hour milling period. These tablets were submitted to two-steps sintering by two different routes: the first one using the levels of 1450ºC for 5 minutes and 1220ºC for 4 hours; the second one at 1220ºC for 2 hours and 1450ºC for 2 hours. After being obtained, the ceramic bodies were characterized by XRD, where Tialite was successfully produced for all adopted formulations and sintering routes. Physical properties measurements (apparent porosity and apparent density, diametrical linear shrinkage), diametrical compression tests and scanning electron microscopy (SEM). From the analyses of the properties and microstructures gotten by the different processing routes, it was noted that the best results were achieved for the composition with excess Alumina. It is worth highlighting the case where sintering was performed by Two-Steps Sintering, mainly between the first group of levels, that resulted in a product with high density, low porosity, high mechanical resistance (breaking strain of 11,87MPa and elastic modulus of 0,370GPa) and more refined microstructure (grain sizes with an average of 2 to 8 microns). The composition with excess Titania was found to be worse than the others, displaying a low mechanical resistance, low density, high porosity, greater grain growth and greater amount of microcracks. The high-energy grinding technique combined with two-steps sintering presented very promising and interesting results, which generates a wide area of ​​technological interest to be further explored.